Fundamental causes of barriers to participation in Alzheimer's clinical research among African Americans. Issue 4 (19th May 2021) - Lincoln, Karen D.; Chow, Tiffany; Gaines, Bryan F.; Fitzgerald, Terence
ABSTRACT: Objectives: African Americans have a significantly higher risk than Whites for developing Alzheimer's disease (AD), but show lower participation in AD clinical trials. Studies of African Americans' involvement in clinical research have identified fear and mistrust of research as barriers to participation. Historical occurrences of unethical research practices are often cited as the source of these attitudes, but underlying factors such as African Americans' experiences of racism and discrimination remain unexplored. The goal of this study was to examine the roles of race and culture in the attitudes and beliefs of African Americans about participating in clinical research. Design: Five focus groups were conducted with 44 African American men and women (aged 50 and over) in a western U.S. state. Participants were asked scripted questions regarding their knowledge and beliefs about AD and their feelings about participating in clinical research. A taxonomy was created to organize results based on participant responses. Results: Four major thematic clusters emerged that influence African Americans beliefs about and participation in clinical research: (a) experiences of unequal treatment and racism, (b) cultural trauma due to historical events and contemporary experiences, (c) racial identity and cultural norms, and (d) the importance of cultural competency and racial congruence in recruitment and research studies. Conclusions: Understanding, acknowledging, and addressing the factors that underlie mistrust and fear of research is important to build trust and to develop culturally appropriate outreach, education, and recruitment strategies that will increase African Americans' participation in clinical research.